From Instagram to Campus: The Impact of Social Media Marketing on Students' Interest through Trust and Brand Recognition - Sriyanto, Agus; Purwanto; Muttaqin, Zaenal (Communication and Islamic Broadcasting Study Program, Faculty of Da'wah and Communication, Universitas Islam Negeri Sunan Kalijaga Yogyakarta, Yogyakarta, Indonesia, 2024)
This study evaluates the influence of social media marketing activities (SMMA) on prospective students' intentions to choose higher education institutions, considering the mediating role of brand recognition and trust. The study was conducted using a quantitative method with the Structural Equation Modeling-Partial Least Squares (SEM-PLS) approach on 400 respondents who were followers of higher education institutions' Instagram accounts. The results showed trust was the most significant mediator between SMMA and prospective students' intentions (β = 0.709, T = 21.629). At the same time, brand recognition played a role in strengthening trust but did not directly influence prospective students' intentions (β = -0.018, T = 0.462). These findings emphasize the importance of building trust through authentic, relevant, and engaging social media content to improve educational marketing effectiveness. The implications of this study suggest that higher education institutions should prioritize trust-based marketing strategies integrated with brand recognition through social media. This strategy includes alumni testimonials, videos of campus atmosphere, and direct interactions that create emotional connections with prospective students.